Flight control system for a variable stability blended-wing-body unmanned aerial vehicle - Blaauw, Deon (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.